(untitled) (Advancements in Homeopathic Research, 2022)
A case of hypothyroidism treated by constitutional homoeopathic medicine is presented here with serial thyroid function test reports. It is worthwhile mentioning here that initially she had high T3, T4 and low TSH for which she was given Neomercazole. Later her TSH became raised and was given Thyrocab, Eltroxin etc. She was perturbed due to fluctuation of her condition between hyper and hypothyroidism and stopped all allopathic medicines. Referred by some of her relatives she consulted us for treatment of her ailment.